Design and realization of distributed control and administration system in fermentation of beer - Yang, Bixiong (2008)
This thesis mainly discusses the principle and design of a control and administration system in fermentation of beer. The system applies multilevel and distributed structure. It consists of a two-level microcomputer system and is provided with numerous advantages, such as simple structure, low cost and high reliability.